Generation X Consumption Behavior Model in Using Digital Transactions - Afni Sirait; Ida Ayu Purnama (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
Technology is a necessity that cannot be separated from today's life. Daily activities become easier, even ignoring distance, space, and time. This convenience provides cost savings, improves the use of time, and even changes business processes. This study aims to analyze the model of consumer behavior of generation X in the use of digital transactions. This research is quantitative research with 73 respondents who meet the qualifications. Data was collected using a questionnaire which was then tested for validity, reliability, and model fit using the WarpPLS 6.0 analysis tool. The results of data processing and testing are carried out; it can be concluded that first, cultural factors mediated by consumption behavior do not directly affect generation X in digital transactions. Second, psychological factors have a direct influence on generation X digital transactions. Consumption behavior as a mediating variable does not have an influence between psychological factors and digital transaction behavior for generation X. The limitation of this study is that the population only focuses on generation X.